PROBLEM OF VITAMIN PROVISION IN SCHOOLCHILDREN IN MODERN CONDITIONS - O.V. Stennikova; L.V. Levchuk; N.E. Sannikova ("Paediatrician" Publishers LLC, 2008)
One of modern actual problems of prophylactic pediatrics is vitamin and mineral provision of schoolchildren. The information about prevalence, etiology, clinical manifestation of vitamin starvation in children was described. The measures of prophylaxis of hypovitaminosis with use of food substances enriched with vitamins and microelements, and with polyvitamin and mineral complexes, fortified drinks, premixes were reviewed. Recommended daily consumption rate of main vitamins and composition of modern vitamin and mineral complexes was indicated.Key words: schoolchildren, vitamins, deficiency, prophylaxis.